Hydrogen and power co-production from autothermal biomass sorption enhanced chemical looping gasification: thermodynamic modeling and comparative study - Liu, Guicai (2022)
Calcium looping and chemical looping technologies envisage advanced solutions for H2 production. This study compared the H2 and power co-production from biomass sorption enhanced gasification (SEG) and sorption enhanced chemical looping gasification (SECLG) under autothermal conditions with thermodynamic simulation. The thermal self-sufficiency of calcination was achieved by splitting biomass for combustion and oxidizing the reduced oxygen carrier, respectively. It was found that SECLG was able to achieve higher energy efficiency (64.6%) than SEG (55.7%) at the optimized carbonator temperature. In both processes, parametric analysis illustrates that under the autothermal-available carbonator temperature range, higher carbonator temperature and fixed carbon conversion are recommended to achieve higher H2 yields and energy efficiencies, owing to lower energy penalty leading to lower requirement of combusted biomass content or Ni/C molar ratio for thermal self-sufficiency. Elevating carbonator pressure slightly improved the energy performance. Regarding CO2 capture through oxyfuel combustion in SEG and SECLG processes, the energy penalty from higher calcination temperature greatly degraded the energy performance, which was even higher than the power consumption of air separation unit. According to exergy analysis, the main exergy destruction occurred at the syngas production section (∼49%). From the view of energy performance, SECLG is a promising autothermal strategy for SEG upgrade.